A Groundwork on Sustainability Leadership with The Rasch Model Approach and Structural Equation Modelling Analysis: Indonesian Employees View - Herlina Maria Grace; Handranata Yunita Wijaya; Rivaldo (E3S Web of Conferences, 2023)
The study is a groundwork of Sustainability Leadership. It aims to explore The aim of this research is to examine spiritual leadership as it relates to sustainability measurement from the perspective of Indonesian employees. This study uses a quantitative approach. Data were obtained from 221 respondents who are Indonesian employees. The collected data was analyzed by Rash Model analysis and Structural Equation Modelling (SEM) Analysis with second-order confirmatory factor analysis. The Rasch Model results found that employees are aware of their company’s sustainable objective. Yet, they still are unable to recognize its impact. The Item measure of Rasch Model shows employees are aware that their current leaders are still reluctant to bring up workplace difficulties. The SEM Findings showed that the three research hypotheses have strong support. First, leadership in sustainability is highly influenced by both vision and hope. Altruistic love, the final factor, has also a big impact on sustainable leadership. Although there have been several past studies, they have been inconsistent and lacking in clarity in developing leadership for sustainability. Hence, this study aims to provide a groundwork of Sustainability Leadership to develop leadership for sustainability measurement.